Clinico-radiological and functional outcome of surgical management of displaced transverse fracture of patella in adults managed by tension band wiring in a tertiary care hospital in North India: a prospective study - Spolia, Pankaj; Nehru, Ashish; Ghani, Abdul; Arfee, Sakib (International Journal of Research in Medical Sciences, 2021)
Background: Patella is the largest sesamoid bone in the quadriceps tendon in the body. The main function of patella is to improve the efficiency of quadriceps muscle by improving the mechanical leverage of the quadriceps muscle. There are various methods used for fixation of these fractures. Tension band wiring (TBW) works by converting tensile forces into compressive forces when movements occur at the knee joint. The aim of our study was to evaluate the clinico-radiological and functional outcome of surgical management of displaced transverse fracture of patella in adults managed by TBW. Methods: This was the prospective study of 22 patients aged 20 to 60 years (mean age 41.4 years) with displaced transverse fractures of patella managed by TBW. Results: The final outcome was observed at 6 months follow up. The results were comparable with the existing literature. Radiological union was achieved within 10 to 16.2 weeks, with an average of 12.4 weeks. Out of 22, (n=16, 72.7%) had excellent outcome, (n=5, 22.7%) had good functional outcome, (n=1, 4.5%) had fair outcome. Complications were observed in 6 (27.3%) patients. Conclusions: It is concluded that the surgical treatment with TBW is the best treatment in the management of displaced transverse fractures of patella.